Aetiological Pattern of Premature Ventricular and Atrial Complexes and their Consequence on Morbidity and Mortality - Kabir, AKM Humayon; Islam, Mohammad Rafiqul; Biswas, Prodip Kumar; Alam, Muhammed Syedul; Mondal, Shekhar Kumar; Karim, Md Enamul; Azhar, MA (Journal of Medicine, 2015)
Background: Arrhythmias are often a manifestation of structural heart diseases but may occur in the context of non cardiac diseases even in an otherwise normal heart. It may be supraventricular or ventricular. Among the arrhythmias premature complexes (ventricular & atrial) are most common type of arrhythmia occurs in patients with or without significant heart disease. Objective: In this study, the aim was to find out the aetiological pattern of premature ventricular and atrial complexes and their consequence on morbidity and mortality, demographical pattern of patients with ectopic beats, to find out aetiological factors leading to development of premature complexes, to find out common clinical presentations and to differentiate the PVCs which are more benign Methods: It was a cross sectional study. This study was carried out in the Department of Medicine and Department of Cardiology of Sir Salimullah Medical College and Mitford Hospital, Dhaka from 1st May 2008 to 15th September 2008. A total 50 consecutive patients irrespective of age, sex and occupation having atrial and ventricular premature complexes on ECG attending at OPD and admitted in indoor were included in this study. Results: Among the three types of premature complexes 9 patients with APCs (also includes 2 patients of premature junctional complex) and 41 patients with PVCs were included. The ratio of patients with PVCs and APCs in this study.8.2: 1.8. In this study 41 patients of PVCs were studied. Among them 37 patient that is 90.3% patients had structural heart disease and the commonest cause was IHD (63.4%), 9.7% had HTN with LVH, 7.3% had DCM, 4.87% had HOCM, one patient had myocarditis ( 2.4%) and one had MVP with sick sinus syndrome (2.4%). Among the 9 patients of APC 4 patients that is 44.44% were suffering from COPD with corpulmonale which was the most commonest cause of APCs. Conclusions: Ventricular arrhythmias are more common than atrial arrhythmia and IHD is the single most common cause of arrhythmia. Ectopic beats in patients with otherwise normal hearts are more prominent at rest and disappear with exercise. Treatment is not necessary, unless the patient is highly symptomatic. J MEDICINE July 2015; 16 (2) : 97-102